Hybrid Organic/Inorganic Photocathodes Based on WS2 Flakes as Hole Transporting Layer Material. Issue 3 (27th November 2020) - Najafi, Leyla; Romano, Valentino; Oropesa‐Nuñez, Reinier; Prato, Mirko; Lauciello, Simone; D'Angelo, Giovanna; Bellani, Sebastiano; Bonaccorso, Francesco
Abstract : The efficient production of molecular hydrogen (H2 ) is a fundamental step toward an environmentally friendly economy. Photocathodes using organic bulk heterojunction (BHJ) films as light harvesters represent an attracting technology for low‐cost photoelectrochemical water splitting. These photocathodes need charge transporting layers (CTLs) to efficiently separate and transport either holes or electrons toward the back‐current collector and electrolyte, respectively. Therefore, it is pivotal to control the energy band edge levels and the work function (WF) of the CTLs to match the ones of the BHJ film, current collector, and electrolyte. Herein, the use of 2D p‐doped WS2 flakes as hole transporting material for H2 ‐evolving photocathodes based on the regioregular poly(3‐hexylthiophene):phenyl‐C61‐butyric acid methyl ester (rr‐P3HT:PCBM) BHJ film is proposed. The WS2 flakes are produced through scalable liquid‐phase exfoliation of the bulk crystal, whereas p‐type chemical doping allows the tuning of the WS2 WF. This approach boosts the performances of the photocathodes, reaching photocurrent densities up to 4.14 mA cm −2 at 0 V versus reversible hydrogen electrode (RHE), an onset potential of 0.66 V versus RHE, and a ratiometric power‐saved metric of 1.28% (under 1 sun illumination). To the best of the authors' knowledge, these performances represent the current record for 2D materials‐based CTLs. Abstract : 2D WS2 flakes are proposed as efficient hole transporting materials for hybrid organic/inorganic photocathodes based on the organic bulk heterojunction photoactive film, reaching a ratiometric power‐saved metric of 1.28%.